Feeding Categorisation of some Caeliferan and Ensiferan species (Insecta: Orthoptera) collected from selected grasslands in Sendai City, Japan - ElSayed, Wael; Kondoh, Michio; Hori, Masatoshi; Nagasawa, Atsuhiko; Nakamura, Koji; Shahenda, Abu ElEla (ENTOMOLOGIA HELLENICA, 2024)
Although orthopteran species have often been regarded as polyphagous herbivores, most of them show variable degrees of diet selectivity and particular food preferences. Still some species possess peculiar feeding categories which need further investigation. An assemblage of 43 orthopteran species, 7 families, 12 subfamilies and 13 tribes was surveyed from five grasslands in Sendai City, Japan to investigate their feeding preferences and were classified into seven main feeding categories based on examination of morpho-mandibular characteristics and postmortem gut content analyses. The forbivorous category was the most dominant, whereas the herbivorous the least common.